Investigating Principals’ Leadership to Develop Teachers’ Professionalism at Madrasah - Warisno, Andi; Hidayah, Nur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study sought to explore the principals’ leadership in private Madrasah Aliyah schools on teachers’ professionalism in the learning process. It applied a quantitative approach with a survey method. Fifty-five teachers served as the samples, which were taken from two private schools in the South Lampung region. Data was collected through a questionnaire. Two instruments were constructed: the first is based on the indicators of leadership using talent management from Gallardo-Gallardo & Thunnissen, and the second is based on teacher competence. The r-test, with the assistance of SPSS 25, was applied to analyze the data. The results indicate an influence of the principals’ leadership on teacher competence. This is evidenced by the results of the r-test showing the value of sig. 0.000. This shows a significant relationship between the principals’ leadership and the teachers’ professionalism in Madrasah Aliyah. Leadership is one of the determining factors in improving teachers’ professionalism, school performance, and a conducive learning process.